Hubungan Waktu Kerja dan Kelelahan Subjektif Dengan Kejadian Kecelakaan Pada Pengemudi Ojek Online - Nurul Dewi Oktavia; Noeroel Widajati; Nala Astari Pramesti (Media Gizi Kesmas, 2022)
Background: The cases of traffic accidents increases year by year as the increase in the number of motorized vehicles. Rapid technological advances have an impact on the progress of the transportation sector, so that the online-based motorcycle taxi application is created. In 2020, 2 million online drivers registered with a company in the transportation sector. Accidents online motorcycle taxi drivers can be caused by several factors, one of which is length of work and subjective fatigue. Work as an online motorcycle taxi requires workers to work in a hot work environment, this triggers fatigue in workers which leads to accidents. This can be exacerbated by working long hours of more than eight hours a day and not being accompanied by adequate rest Objectives: The objective of this study was to determine the strong relationship between water consumption, work Duration and subjective fatigue with the accidents among online motorcycle taxi drivers. The independent variables in this study is work duration and subjective fatigue, while the dependent variable was the incidence of accidents. Method: This study was analytical and observational, with a cross-sectional design. The subject of the study was an online motorcycle taxi driver in the Sidoarjo Regency area with up to 110 respondents. Result: The results of the analysis showed that there was a positive and a weak correlation between working hours (CI=0.209), while there was a fairly strong correlation with a positive direction for subjective fatigue (r=0.326) with the incidence of accidents on online motorcycle taxi drivers. Conclusion: The analysis show that there is a weak relationship between work duration and the incidence of accidents for online motorcycle taxi drivers, while there is a fairly strong relationship between subjective fatigue and accidents. From the results of data analysis, the direction of the relationship between two independent variables is positive, it meaning that the longer work duration will cause an increase in fatigue and the incidence of work accidents.